Controlled surface wrinkling as a novel strategy for the compressibility-tunable PZT film-based energy harvesting system. (January 2021) - Xue, Zhiming; Wang, Changguo; Tan, Huifeng
Abstract: Using a controlled surface wrinkling strategy, we designed a flexible energy harvesting system made from a compliant substrate, stiff skin layer, a thin PZT film, and an interdigitated electrode sandwich structure. This energy harvesting system, which operates under compressing and releasing operating modes that are common in nature and engineering, accommodates orders-of-magnitude increases in maximum compressive strain without fracture. This increased range allows the system to be used for more applications. We systematically explored the effects of different parameters on system compressibility and piezopotential output performance. These analytical results guide the design for enhancing compressibility or piezopotentials of the energy harvesting system.